The complete plastid genome sequence of Chloranthus fortunei (A. Gray) Solms-Laub. in Chloranthaceae - Jong-Soo Kang; Bo-Yun Kim; Ki-Oug Yoo (Mitochondrial DNA. Part B. Resources, 2022)
Chloranthus fortunei (A. Gray) Solms-Laub. is a perennial herb in a basal angiosperm family Chloranthaceae. Here, we reported the complete plastid genome of C. fortunei using Illumina short-read data. The total genome size was 157,063 bp in length, containing 79 protein-coding genes, 30 tRNA genes, and four rRNA genes. The gene content and order were consistent with previously reported Chloranthus plastid genomes. The overall GC content of the C. fortunei plastid genome was 39.0%. In the phylogenetic result, genus Chloranthus was monophyletic and divided into two subclades: C. japonicus+C. angustifolius+C. fortunei, and C. henryi+C. spicatus+C. erectus. Our phylogenetic result was consistent with previous phylogenetic studies, and was supported by a previously proposed infrageneric classification of the genus Chloranthus.